Isochromosome Mosaic Turner Syndrome with Delayed Growth and Puberty: A Case Report - Tamrakar, R.; Rai, A.; Maskey, R. (Journal of Diabetes and Endocrinology Association of Nepal, 2023)
Isochromosome Mosaic Turner Syndrome, a variant of Turner syndrome which has a milder presentation, can present without the typical features of Turner syndrome. Evaluation of Turner syndrome with karyotyping has to be performed in females presenting with short stature. We present a case of 15 years girl who presented with delayed growth and puberty with primary amenorrhea and hyperthyroidism. Cytogenetic study of peripheral blood revealed 45,X [31]; 46, X,i(X)(q10) [19] suggestive of Isochromosome Mosaic Turner Syndrome.